Reflections and perspectives on the uses of social networks in education. A case study in quito-Ecuador - Hermann-Acosta, Andrés (2019)
This research focused on determining how the use of web 2.0 resources such as social networks is allowing the construction of learning processes, in non-formal educational contexts mediated by the use of digital technologies. To obtain the data a mixed research method was applied, including a review of high-impact secondary sources, as well as the application of a case study, based on surveys of high school students in Quito-Ecuador. It was established that 80% of young media users have used social networks for educational purposes, an aspect that has made it possible to conclude that the use of digital technologies is not only helping to promote aspects such as communication and entertainment, but also incorporate invisible learning to their cognitive processes.